TERAPIA COMBINADA DE CARVACROL COM TREINAMENTO FÍSICO AERÓBIO REDUZ O RISCO CARDIOVASCULAR DE RATOS ESPONTANEAMENTE HIPERTENSOS. - COSTA, Herikson Araujo (2021)
Introduction: systemic arterial hypertension (SAH), characterized by the maintenance of high blood pressure levels, is considered the main risk factor for the triggering of cardiovascular disorders (CVDs). Therefore, it is salutary to investigate new therapies, especially non- medications, that can assist in the treatment of SAH and reduce cardiovascular risks. In this context, carvacrol, a monoterpene classified as a major compound in oregano, appears as a promising option for use in the treatment of CVDs, since its anti-inflammatory, antioxidant, antihypertensive and cardioprotective properties are already known. Another non-drug therapy widely studied for the treatment of CVDs is aerobic physical training, which can provide modular effects on lipid parameters, blood pressure and cardiac remodeling. Objective: to investigate whether aerobic physical training enhances the reduction of cardiovascular risk in spontaneously hypertensive rats treated with 20 mg/kg of carvacrol. Method: the experimental design was composed of six groups, 1) normotensive control group (Wistar), 2) hypertensive control (SHR), 3) positive control treated with amlodipine (Aml-20mg), 4) group treated with carvacrol (Carv-20mg), 5) treated with exercise (Exer) and 6) treated with exercise and carvacrol (ExerCarv), who underwent four weeks of treatment and weekly heart rate, systolic, diastolic and mean blood pressure. Before and at the end of the treatment protocol, the animals were submitted to a test of maximum physical effort on a treadmill. At the end of the treatment, vascular reactivity tests were performed, in addition to biochemical measurements of blood glucose, urea, creatinine, AST, ALT, triglycerides, total cholesterol, HDL-C, LDL-C, VLDL- C, calculations of atherogenic indexes, weight organ relative and histopathological analysis of cardiac perivascular tissue. Results: the treated groups did not experience renal and hepatic toxicity, since there was a reduction in serum urea and AST levels. The proposed treatment program reduced blood pressure levels of hypertensive animals from the first week, with hypertension being controlled after four weeks of treatment. The ExerCarv group experienced greater magnitudes of BP reduction when compared to the other groups, including the group treated with amlodipine (ExerCarv: ∆ SBP = 88.17 ± 10.0 mmHg; ∆ DBP = 66.17 ± 31.89 mmHg; ∆ MAP = 73.5 ± 20.0 mmHg). We can still observe a decrease in vascular reactivity, with the treated groups developing less vascular tension (Emax) when exposed to cumulative concentrations of norepinephrine and calcium. The Carv-20mg group demonstrated a discreet effect on lipid variables, reducing only serum levels of triglycerides, LDL cholesterol and atherogenic indexes, while trained groups (Exer and ExerCarv) managed to modulate all lipid variables regardless of the use of carvacrol. It was also possible to observe a maintenance of the relative weight of the heart (g / 100g) (Wistar: 0.42 ± 0.03; SHR: 0.48 ± 0.03; Aml-20mg: 0.39 ± 0.03; Char -20mg: 0.41 ± 0.04; Exer: 0.42 ± 0.02 and ExerCarv: 0.41 ± 0.03), as well as changes in the level of cardiac tissue in the treated animals, with the animals in the group Untreated SHR, with hypertrophy of perivascular tissue and more swollen cardiomyocytes. Conclusion: four weeks of treatment with carvacrol (orally) or aerobic training, of SHR animals is efficient for regularization of BP, and the interaction between these therapies provides a greater magnitude of blood pressure reduction. We also concluded that aerobic physical training modulates the lipid variables associated with cardiovascular risk, regardless of the use of carvacrol. Finally, treatment with carvacrol and / or aerobic training preserves the cardiac muscle, preventing hypertrophy and tissue disorders related to injury to this organ by hypertension.